2015
DOI: 10.1371/journal.pone.0143377
|View full text |Cite|
|
Sign up to set email alerts
|

Bioinformatics Analysis of the Effects of Tobacco Smoke on Gene Expression

Abstract: This study was designed to explore the effects of tobacco smoke on gene expression through bioinformatics analyses. Gene expression profile GSE17913 was downloaded from the Gene Expression Omnibus database. The differentially expressed genes (DEGs) in buccal mucosa tissues between 39 active smokers and 40 never smokers were identified. Gene Ontology (GO) and pathway enrichment analyses of DEGs were performed, followed by protein-protein interaction (PPI) network, transcriptional regulatory network as well as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…The dataset consists of 52 human samples; after excluding 4 samples that did not pass quality control, 26 normal kidney samples and 22 CKD samples were used to conduct DEGs analysis. DEGs were defined by the Bioconductor/R limma package as previously described [ 58 ]. Cut-off values of P < 0.01 and Fold Change |FC| ≥ 2 were applied.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset consists of 52 human samples; after excluding 4 samples that did not pass quality control, 26 normal kidney samples and 22 CKD samples were used to conduct DEGs analysis. DEGs were defined by the Bioconductor/R limma package as previously described [ 58 ]. Cut-off values of P < 0.01 and Fold Change |FC| ≥ 2 were applied.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to human malignancies, there was a clear increase in CYP1B1 promoter CpG island methylation level in isoniazid-induced liver injury in rats (Li et al, 2018). Interestingly, bioinformatics analyses by Cao et al identified CYP1B1 as a potential target in smoking-mediating malignancies (Cao et al, 2015). Experimental analysis further demonstrated that hypo-methylated CYP1B1 was up-regulated in current smokers (Tsai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to studies assessing lung cancer via bioinformatics tools 15 19 , a few studies have focused on smoking with a systems biology approach; for instance, expression-based network analysis and assessment of protein-protein interactions have revealed changes in human blood 20 , human buccal mucosa 21 , and mouse lung samples 22 due to cigarette exposure. For exhibiting the direct correlation between smoking and lung cancer, Ying Liu et al .…”
Section: Introductionmentioning
confidence: 99%